Tugas Dan Fungsi Panwaslu Dalam Penyelesaian Pelanggaran Pemilu Di Kota Jambi - Nazifah Nazifah (Jurnal LEX SPECIALIS, 2011)
Establishment of specialized agencies in the administration of elections members of the House of Representatives / People 'Region, is expected all things relating to the election runs smoothly. In reality, however, still found many violations of the provisions of the general election which proved many cases of electoral malpractices that go to the Election Supervisory Committee for City of Edinburgh and Edinburgh District Court. The number of violations of the election, especially in the legislative elections, has a duty to uncover the Election Supervisory Committee and complete implementation of the principle to the general election itself. Duties and functions of the Election Supervisory Committee is very heavy and very possible a lot of constraints encountered in the execution of his duty. Key Note : Panwaslu Election Violations In Settlement